2011
DOI: 10.1017/s002211201000621x
|View full text |Cite
|
Sign up to set email alerts
|

Very-large-scale motions in a turbulent boundary layer

Abstract: Direct numerical simulation of a turbulent boundary layer was performed to investigate the spatially coherent structures associated with very-large-scale motions (VLSMs). The Reynolds number was varied in the range Reθ = 570–2560. The main simulation was conducted by using a computational box greater than 50δo in the streamwise domain, where δo is the boundary layer thickness at the inlet, and inflow data was obtained from a separate inflow simulation based on Lund's method. Inspection of the three-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
137
4
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(172 citation statements)
references
References 41 publications
28
137
4
1
Order By: Relevance
“…Other higher-level and larger-scale structures in the hierarchy (57)(58)(59) are not the focus of this paper. However, we note that the wake region ð0.5 < y=δ < 1Þ and the BTFTI region are densely populated by groves of concentrated large-scale hairpin vortices (Movie S7).…”
Section: Resultsmentioning
confidence: 99%
“…Other higher-level and larger-scale structures in the hierarchy (57)(58)(59) are not the focus of this paper. However, we note that the wake region ð0.5 < y=δ < 1Þ and the BTFTI region are densely populated by groves of concentrated large-scale hairpin vortices (Movie S7).…”
Section: Resultsmentioning
confidence: 99%
“…They interpreted that the apparent wavering of the VLSM on a scale of O(6δ) in the turbulent boundary layer (TBL) is induced as a consequence of spanwise offset LSMs rather than through sinusoidal perturbation of an otherwise straight, streamwise-aligned sequence of LSMs. Through time-evolving instantaneous fields, Lee and Sung 6 and Lee et al 9 provided clear evidence of the formation of VLSM in which adjacent packet-type structures combine to form VLSM on the order of O(18δ), as conjectured by Kim and Adrian. 10 Due to the significant importance of LSMs in wall-bounded turbulent flows, extensive studies of structures over rough-wall TBLs have been performed.…”
Section: Introductionmentioning
confidence: 80%
“…[1][2][3] These structures correspond to bulges or hairpin packets of large-scale motions (LSMs) with streamwise extents on the order of 1-3δ and very-largescale motions (VLSMs) with sizes in the range of 10-30δ, where δ is the boundary layer thickness. [1][2][3][4][5][6] Hairpin packets consist of a coherent group of hairpin vortices aligned along the streamwise direction. 5 These structures create elongated low-momentum regions beneath them which are bounded in the spanwise direction by high-momentum regions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sillero et al (2014b) found that the self correlation of u in the wall parallel plane conditioned to u < 0 is longer than that conditioned to u > 0, independent of the wall distance. But results in Lee & Sung (2011) It is well accepted that closer to the wall structures are smaller while the opposite when farther away from the wall (Jiménez, 2012). So the downward moving v is supposed to bring large scales to the near wall region while the opposite for the upward v, i.e.…”
Section: High and Low Streamwise Velocities Associated With Q4s And Q2smentioning
confidence: 97%